Production and Detoxification of Inhibitors during the Destruction of Lignocellulose Spatial Structure - Xingxing Luo; Baiquan Zeng; Yanan Zhong; Jienan Chen (BioResources, 2021)
Lignocellulosic biomass is a renewable resource that is widely abundant and can be used to produce biofuels such as methanol and ethanol. Because biofuels have the potential to alleviate shortages of energy in today’s world, they have attracted much research attention. The pretreatment of lignocellulose is an important step in the conversion of biomass products. The pretreatment can destroy the crosslinking effect of lignin and hemicellulose on cellulose, remove lignin, degrade hemicellulose, and change the crystal structure of cellulose. The reaction area between the enzyme and the substrate is enlarged, and the yield of subsequent enzymatic hydrolysis and microbial fermentation products is significantly increased. Conventional pretreatment methods help convert lignocellulosic material to sugars, but the treatments also produce some inhibitors, which are mainly organic acids, aldehydes, phenols, and other substances. They may affect the subsequent saccharification and growth of fermentation microorganisms, thereby reducing the bioconversion of the lignocellulose. It is therefore necessary to take effective means of detoxification. This paper reviews lignocellulose pretreatment methods, with an emphasis on inhibitors and their management. A summary is provided of detoxification methods, and the future use of lignocellulosic biomass for fuels prospects.